PENGARUH LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS PADA PT BANK RAKYAT INDONESIA (Persero) Tbk CABANG MAKASSAR AHMAD YANI - Abdul Khalik (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This study aims to determine the effect of the loan to deposit ratio to profitability at Bank BRI branch Ahmad Yani Makassar. The results showed that the average level of LDR and profitability during the 3 (three) years as from the year 2012 to 2014 has increased. Based on the results of a simple linear regression analysis, described the